Inseminação artificial em ovelhas - Fonseca, Phellipe de Oliveira (2009)
In sheep, several methods of artificial insemination (AI) have already been described. Currently, two methods are most used in the field, transcervical and laparoscopic AI. However, these are methods that imply discomfort to the animal, such as traction of the vaginal wall with surgical forceps, lateral to the cervix, in addition to the Trendelenburg position (head slope, at an angle of 30 to 45 °). Thus, this study aimed to study techniques that provide greater comfort to the animal, during the procedure. 43 Morada Nova sheep were used, divided into four groups: 11 vaginal AI, 11 vaginal AI associated with cervical dilators (misoprostol and terbutaline), 10 cervical AI and 11 laparoscopic AI in lateral decubitus. The estrous cycle was synchronized with progestins and equine chorionic gonadotropin (eCG). No complications were observed during or after the procedures. The pregnancy diagnosis was made at 30 and 60 days after the AI. The pregnancy rate was 10% in females vaginally inseminated with and without the use of dilators and 54% in females inseminated by laparoscopy. No female inseminated through the cervical route was pregnant at 30 and 60 days. It was concluded that the laparoscopic insemination technique in lateral decubitus was performed successfully, reduced discomfort and presented an acceptable pregnancy rate.